Análises dos fatores para implantação e consolidação de um banco comunitário em território popular: o caso do banco comunitário da Cidade de Deus - Oriente, Anderson Carlos Nogueira (2019)
This thesis presents the analysis of factors for the implantation and consolidation of a community bank in popular territory. After reviewing the literature related to the theme, the field research carried out in the community banks of the states of Rio de Janeiro and Ceará. And participation in events related to the theme of solidarity economy and financial education. He considered it important to structure the methodology of the Instituto Banco Palmas as a factor of implementation, and for consolidation after the field research, where we conducted the case study of the Community Bank of the City of God, in the Cidade de Deus Housing Estate, neighborhood of the city of Rio de January, we built three variables: 1) the role of the territory; 2) the political articulation; and 3) the organizational aspect. The research focuses on the analysis of these factors to build meaningful alternatives for the implantation and consolidation of a community bank in a popular territory.